The smart money guide to real estate investing - Willis, Gerri (Jonh Wiley, 2003)
As the financial markets waiver and mortgage rates continue to be near their historical lows, many people are looking to real estate as an investment alternative to stocks and mutual funds. But for those with little real estate investing experience, entering into this arena can be intimidating. The SmartMoney Guide to Real Estate Investing has been written to help anyone interested in real estate gain a firm understanding of real estate pitfalls and potentials. It clearly walks readers through real estate basics to educate individuals who may be looking to buy a home for themselves or merely as an investment. Information on mortgages, selecting property, working with brokers, and renovations are discussed along with many other real estate topics including: investing in single-family homes; the purchase of homes with low down-payments; performing renovations that will increase property value; flipping homes for profit; and navigating the turbulent waters of vacation and retirement home buying. Filled with expert knowledge that only SmartMoney could provide, The SmartMoney Guide to Real Estate Investing is the best choice for learning about real estate investing.